A Review of the Epidemiology, Pathophysiology, and Efficacy of Anti-diabetic Drugs Used in the Treatment of Nonalcoholic Fatty Liver Disease - Manka, Paul P.; Kaya, Eda; Canbay, Ali; Syn, Wing-Kin (Digestive diseases and sciences, 2021)
In recent years, epidemiological studies have consistently demonstrated that the coexistence of nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM) is strongly associated with increased mortality and morbidity related to hepatic- and extrahepatic causes. Indeed, compared with the general population, patients with T2DM are more likely to be diagnosed with more severe forms of NAFLD (i.e., nonalcoholic steatohepatitis (NASH) with liver fibrosis). There is an ongoing debate whether NALFD is a consequence of diabetes or whether NAFLD is simply a component and manifestation of the metabolic syndrome, since liver fat (steatosis) and even more advanced stages of liver fibrosis can occur in the absence of diabetes. Nevertheless, insulin resistance is a key component of the mechanism of NAFLD development; furthermore, therapies that lower blood glucose concentrations also appear to be effective in the treatment of NAFLD. Here, we will discuss the pathophysiological and epidemiological associations between NAFLD and T2DM. We will also review currently available anti-diabetic agents with their regard to their efficacy of NAFLD/NASH treatment.